How Digital Content Influences Visit Intention Through the Psychological Evaluation Process of Potential Tourists - Aini, Nurul Qurrotul; Churiyah, Madziatul; Dhewi, Titis Shinta (Dinasti Publisher, 2026)
The purpose of this study is to examine the influence of firm-generated content (FGC) and user-generated content (UGC) on visit intention to Pahawang Island through psychological evaluation processes presented by destination image and perceived value. This study employed a numerical approach with a causal research design. Data were gathered through an online survey administered to 216 TikTok users who had been exposed to travel agent (FGC) and tourist content (UGC) about Pahawang Island, but had never visited the destination. The Partial Least Squares with Structural Equation Modeling (PLS-SEM) was applied, with assistance from SmartPLS software, to analyze data. The results demonstrate that FGC and UGC had a positive and significant effect on destination image and perceived value, while the direct influences of FGC and UGC on visit intention were insignificant. Conversely, destination image and perceived value are confirmed to have a significant effect on visit intention, and act as mediators. These findings suggest that digital content on TikTok influences visit intention through a psychological evaluation process, not through direct effects. These findings facilitate the advancement of a theory by expanding the S-O-R (Stimulus-Organism-Response) framework and provide practical implications for social media-based destination marketing on TikTok.